2022
DOI: 10.3390/atmos13091493
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Urban Thermal Environment Based on Multi-Dimensional Nature and Urban Form Factors

Abstract: The urban thermal environment is affected by multiple urban form and natural environment factors; research on the accurate prediction of the urban thermal environment, considering the interaction among different urban environmental factors, is still lacking. The development of a machine learning model provides a good means of solving complex problems. This study aims to clarify the relationship between urban environmental variables and the urban thermal environment through high-precision machine learning model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…[19][20][21][22][23][24]. To estimate the impact of urban development on the local climate, modeling-based research has been increasingly conducted in major metropolitan areas around the world [25,26]. Studies have shown that urban development significantly alters the surface energy balance and hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24]. To estimate the impact of urban development on the local climate, modeling-based research has been increasingly conducted in major metropolitan areas around the world [25,26]. Studies have shown that urban development significantly alters the surface energy balance and hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The standing building infrastructure also alters airflow, energy absorption, and atmospheric heat transfer in the city, resulting in profound changes in meteorological environments, such as changes in the temperature, humidity, and wind [27][28][29]. In recent years, more and more studies have explored the impact of three-dimensional development environments on urban microclimates, establishing statistical relationships between observed meteorological elements or land surface temperatures and urban development environments using machine learning methods [26,30,31]. Some scholars have simulated the urban wind-heat environment to explore the effects of different scales of the urban natural and built environment elements on the wind-heat environment.…”
Section: Introductionmentioning
confidence: 99%
“…Different landscape types have different thermal radiation characteristics, which will lead to change in the spatial relationship between urban landscape pattern and thermal environment [7][8][9][10]. At the same time, population migration significantly increases the heat discharge capacity of cities, accelerating different urban thermal environmental effects [11][12][13][14][15][16][17]. The obvious characteristics of urban thermal environment and heat island effect have brought a series of negative effects on urban ecosystem structure and residents' health [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%